Characteristic of Allergen Protein of Nila Baby Fish (Oreochromis niloticus) and Its Processed Product - Hendra Wijaya; Sri Yadial Chalid; Ning Ima Arie Wardayanie; Widyaningsih Widyaningsih; Santi Ariningsih (Syarif Hidayatullah State Islamic University, 2020)
Allergen protein is a protein that could triggers allergy reaction. This study purposes to examine the characteristic of allergen protein of unripe, boiled, and fried nila baby fish. Characteristic of allergen protein were observed by electrophoresis and immunoblotting method, while the determination of protein concentration was observed by Bradford method. Identification of the used nila baby fish was accomplished in Faculty of Fishery and Marine Science of IPB. The result of identification showed that the used nila baby fish was Oreochromis niloticus. The proximate analysis of unripe, boiled, and fried nila baby fish resulted water content ranged from 19.16%-23.68%, fat content ranged from 1.03%-20.44% and carbohydrate content ranged from 0.16%-20.27%. Protein concentration of unripe, boiled, and fried nila baby fish extract respectively were 1963.45 mg/L; 699.82 mg/L; 607.79 mg/L. The band amount of allergen protein of unripe, boiled, and fried nila baby fish which was detected by electrophoresis, respectively were 16 of protein band, 26 of protein band and 16 of protein band. The immunoblotting showed that the sum of respondent who contained specific IgE that can bind with allergen protein of boiled and fried nila baby fish were more than allergen protein of unripe nila baby fish. It indicated that the processing process by boiling and frying would increase allergenicity toward nila baby fish.